Spring Water Quality Distribution Characteristics and Evaluation of Luannan Coastal Wetland in Hebei Province - LIU Pengfei; WANG Jiuliang; LIU Dewu; LI Yue (Haiyang Kaifa yu guanli)
This paper explores the distribution characteristics and influencing factors of nitrogen and phosphorus nutrients in the spring water body of Luannan Coastal Wetland in Hebei Province, based on data such as nitrogen and phosphorus nutrient concentrations and physical and chemical indicators in 2022. The eutrophication status of the wetland was evaluated using single factor pollution index method, Nemero comprehensive index method, and comprehensive nutrient status index method. The evaluation results were discussed and analyzed. The results showed that the water quality detection results of Luannan Wetland showed an average permanganate index of 11.27 mg/L, ammonia nitrogen of 0.13 mg/L, salinity of 53.57 mg/L, total nitrogen of 3.17 mg/L, total phosphorus of 0.32 mg/L, and chlorophyll a The average is 25.44 μg/L. The pollution level of total nitrogen and total phosphorus in Luannan Wetland is relatively high, with concentrations exceeding the standard concentration multiple, reaching a maximum of 10 times or more. Among them, the stations exceeding the standard of total nitrogen and total phosphorus are mainly concentrated in the northern residential areas of wetland, and the stations exceeding the standard of permanganate index are mainly distributed in the northeast and western aquaculture ponds and salt pans. The single factor index method evaluation result of surface water in Luannan Coastal Wetland is inferior to Class V, with serious pollution and severe eutrophication of wetland water quality. The main sources of pollution are aquaculture wastewater and domestic sewage. The severe fragmentation of wetlands caused by enclosed aquaculture, and the poor connectivity of water bodies, which makes it difficult for nutrients to spread, are the main factors causing eutrophication.